2011
DOI: 10.1159/000327131
|View full text |Cite
|
Sign up to set email alerts
|

Does Uremia Cause Vascular Dysfunction

Abstract: Vascular dysfunction induced by uremia has 4 main aspects. (1) Atherosclerosis is increased. Intima-media thickness is increased, and animal studies have established that uremia accelerates atherosclerosis. Uremic toxins are involved in several steps of atherosclerosis. Leukocyte activation is stimulated by guanidines, advanced glycation end products (AGE), p-cresyl sulfate, platelet diadenosine polyphosphates, and indoxyl sulfate. Endothelial adhesion molecules are stimulated by indoxyl sulfate. Migration and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
96
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(101 citation statements)
references
References 134 publications
0
96
0
3
Order By: Relevance
“…They make up a group whose numerous members differ in their water solubility, protein-binding capacity, molecular weight, pattern of removal by dialysis, biological properties and potential to produce clinical symptoms [2,3,11,19,20].…”
Section: Identification Characterization Analytical Determination Amentioning
confidence: 99%
“…They make up a group whose numerous members differ in their water solubility, protein-binding capacity, molecular weight, pattern of removal by dialysis, biological properties and potential to produce clinical symptoms [2,3,11,19,20].…”
Section: Identification Characterization Analytical Determination Amentioning
confidence: 99%
“…In another study, PD patients were found to have higher ADMA levels than controls, but endothelial dysfunction in these patients could not be explained by this increased level (23). Many mechanisms are known to be effective on endothelial dysfunction in uremic patients, increased ADMA level being only one of them (24). There are concordant and discordant results in larger broadbased studies carried on HD patients (21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Many mechanisms are known to be effective on endothelial dysfunction in uremic patients, increased ADMA level being only one of them (24). There are concordant and discordant results in larger broadbased studies carried on HD patients (21)(22)(23)(24)(25). The reason for lack of evidence for correlation in patients with ESRD having many comorbidities, while the evidence is stronger in non-uremic patients with lower cardiovascular risk, may be coexistence of many cardiovascular risk factors (26).…”
Section: Discussionmentioning
confidence: 99%
“…Субстратом для развития ССЗ с возрастом являются изменения в артериаль-ной стенке: эндотелиальная дисфункция, уси-ление жесткости артериальной стенки, атеро-склероз. На фоне ХБП, а в наибольшей степени при терминальной почечной недостаточности, наблюдается усиление изменений в артериаль-ной стенке [10].…”
Section: The Relationship Of Kidney Function With Arterial Wall Condiunclassified